Pengaruh Lingkungan Kerja Fisik dan Kepemimpinan Transaksional Terhadap Kinerja KaryawanN Pada PT. SAMESTA ENGINEERING PEKANBARU - Harwina, Yulia (Akuntansi & Ekonomika, 2018)
This study took place research at PT. Samesta Engineering Pekanbaru with Jl. Parit Indah Office Grand Sudirman No. D 6 Pekanbaru. The purpose of this study to determine the effect of physical work environment and transactional leadership partially and simultaneously on employee performance and to determine which variables are the most dominant influence on employee performance. To achieve these objectives the research is done by using the sample of 43 people, using the Census. Data analysis method using simultaneous test and partial test (multiple linear regression analysis with SPSS Windows version 20). The test results in variable physical work environment factors and transactional leadership partially and simultaneously influence the performance of employees at PT. Samesta Engineering Pekanbaru. Where is the most dominant factor influencing performance is the physical work environment factors. Recommendations to the authors propose is expected PT. Samesta Engineering Pekanbaru to be able to further enhance the physical work environment variables for the physical work environment affects the performance by gaining an average of responses agreed. Where the presence of adequate physical working environment at PT. Samesta Engineering Pekanbaru then it will be able to improve the performance of employees